Theoretical and Practical Considerations Regarding the Risk Factors in Organizational Communication. (2015) - Cecan, Simion; Marian, Liviu
Abstract: The papers in this field point out the major role of the informatics systems, a component of the organizational communication, in materializing the finality of the productive companies. Organizational communication must be included in the general and generous concept of the General Theory of Systems (GTS), a method that explains and investigates the elements and the functions of the respective process. GTS allows us to make an inventory and to manage the events with unwanted impact known as risks. This current paper proposes an original systemic vision on risk management in organizational communication and presents the results of a research on risk perception in organizational communication at the level of top managers, in Mures County. The paper is original from the theoretical point of view, presenting an inventory of the risk factors specific to organizational communication, including a systematic approach using a complex structure. The paper is also original from the practical stand point because it is based on a practical questionnaire regarding the risk perception at the level of top managers in Romania.